Monocultural Authority and Imperialist Extraction in the Primary-Secondary Source Division: Implications for Library Instruction - Watkins, Alexander; Randall, Kathryn (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
This paper examines one way that colonial logic is embedded in western academic practices. It argues that the conventional dichotomy between primary and secondary sources in the humanities and social sciences reflects western monocultural hegemony in its application to non-western knowledges. In these fields, primary sources are treated as objects, analysed as evidence, and used as data, while secondary sources get to act as subjects and are engaged with as experts. This paper identifies a problematic dynamic where Indigenous authorities whose expertise does not align with western academic norms are categorised and used as primary sources, thereby stripping them of their agency and subjectivity. Their knowledge is extracted, commodified, and appropriated for the benefit of the west. Further, the paper critiques the role of librarians and archivists in perpetuating this colonial logic through their instruction practices and professional frameworks and standards, especially around primary source literacy and evaluating authority. These practices promulgate monocultural tools through which knowledge is extracted and evaluated. This paper calls on librarians to critically assess their role in maintaining colonial structures that continue to marginalise Indigenous Knowledge.